Bisphenols Threaten Male Reproductive Health via Testicular Cells - Adegoke, Elikanah Olusayo; Rahman, Md Saidur; Pang, Myung-Geol (Frontiers in Endocrinology, 2020)
Male reproductive function and health are largely dependent on the testes, which are strictly regulated by their major cell components, i.e. Sertoli, Leydig, and germ cells. Sertoli cells perform a crucial phagocytic function in addition to supporting the development of germ cells. Leydig cells produce hormones essential for male reproductive function, and germ cell quality is a key parameter for male fertility assessment. However, these cells have been identified as primary targets of endocrine disruptors, including bisphenols. Bisphenols are a category of man-made organic chemicals used to manufacture plastics, epoxy resins, and personal care products such as lipsticks, face makeup and nail lacquers. Despite long-term uncertainty regarding their safety, bisphenols are still being used worldwide, especially bisphenol A. While considerable attention has been paid to the effects of bisphenols on health, current bisphenol-related reproductive health cases indicate that greater attention should be given to these chemicals. Bisphenols, especially bisphenol A, F, and S, have been reported to elicit various effects on testicular cells, including apoptosis, DNA damage, disruption of intercommunication among cells, mitochondrial damage, disruption of tight junctions, and arrest of proliferation, which threaten male reproductive health. In addition, bisphenols are xenoestrogens, which alter organs and cells functions via agonistic or antagonistic interplay with hormone receptors. In this review, we provide in utero, in vivo, and in vitro evidence that currently available brands of bisphenols impair male reproductive health through their action on testicular cells.